THE IMPACT OF INCLUSIVE LEADERSHIP ON EMPLOYEE ENGAGEMENT AND INNOVATION - Pagisi, Evawarta I (Penelitian dan Pengembangan Ilmu, 2024)
In the context of increasingly diverse and dynamic work environments, inclusive leadership has emerged as an important approach to increasing employee engagement and innovation. This research aims to identify the main characteristics of inclusive leadership that contribute to increased employee engagement. Through the Systematic Literature Review (SLR) method, 22 relevant articles were analyzed to explore the attributes of inclusive leadership and their impact on employee engagement. Findings show that characteristics such as open communication, empathy, fairness in decision making, empowerment, cultural awareness, and support for employee development significantly increase employee engagement. This research provides valuable insights for organizations in developing more inclusive leadership strategies, which in turn can improve employee productivity and well-being. The results of this study also suggest the need for further research to explore the long-term impact of inclusive leadership in various industrial contexts.